A Student’s Perspective Of Scamper Technique Used For Multimedia Asset Creation - Kok, Yew Ang; May , Chan Yuen (2016)
The purpose of this paper was to investigate the effectiveness of SCAMPER technique based on students’ perspective. SCAMPER is an abbreviation of a seven-step idea generation technique which consists of Substitute, Combine, Adapt, Magnify, Modify, Put to another use, Eliminate and Rearrange. Creating a multimedia asset can be a challenge especially when the students are required to produce in a short time of period given. Hence this idea generation technique is introduced to the students to enhance their creativity and speed in their asset creation. This study used a qualitative approach to better understand the difficulties students faced and the effectiveness of SCAMPER technique in creating assets for design and multimedia production. The multimedia assets that the students created is not limited only to video, audio, graphic design, text or 3D models but could be a combination of any of the mentioned medium (Wang, et al, 2012).